A Critical Book Review of Civil Society and Democracy in the Middle East - SeyedSaeid ZahedZahedani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This book follows a political development in the Middle East. After World War II, at the time of the U.S. investments in Europe and the third world countries, development became a subject of study in social sciences.  According to Modernization Theories, political development should follow economic and cultural developments. Mostly at this phase, Islamic societies resist development because of its secular, humanist, and experimental sciences bases.  Thereby, development confronts challenges in Islamic countries.  Articles of this book explain hardships of liberal democracy in Islamic countries and suggest some solutions.  They believe there should be negotiations between Iran and the U.S., the top powers of the region, in order to avoid conflicts. Other suggestions are the interpretation of religious texts according to liberal principles, promotion of gender equality, and enhancement of women's' participation in social life.